ANALISIS KOMUNIKASI HUMAS PEMERINTAH KABUPATEN SAMPANG(Studi Kasus Informasi Organisasi di Dinas Komunikasi dan Informatika) - Rizqi Fadlilatul Ula (2022)
The Office of Communication and Information in Sampang Regency has internal problems in the form of the Head Office Service who is less communicative to his employees and results in tiered communication and uneven distribution of information. This study aims to determine the implementation of organizational information and communication at Diskominfo based on the SWOT method and the AHP method. This research uses Karl Weick's Organizational Theory and Chester Barnard's Theory of Authority. The research method used is descriptive qualitative, case study approach, and constructivism paradigm. Data was collected by means of interviews with research informants and participatory observation. Data analysis was carried out by coding process, SWOT method, and AHP method. The result of this research is the analysis of organizational information produces a communication strategy through the SWOT method and the AHP method. The total value of IFAS is 4,3 and the total value of EFAS is 4,2 in the SWOT analysis, indicating that Diskominfo has exprienced rapid growth in the weekly meeting and Tiktok programs in Sampang Regency. The SWOT strategy matrix produces six communication strategies. The AHP method begins with determining priority goals, namely the implementation of the Diskominfo strategy, namely the creation of open communication and information dissemination between each hierarchy with a weight of the 0,42. The priority in supporting the strategy is Tiktok, Sampang Regency is superior to other regencies in Madura with 20.600 followers with a weight of 0,2. The strategic priority actor is the Head of Communication and Information Technology with a weight of 0,16. An alternative priority strategy is to evaluate and strengthen the weekly meeting system with a weight of 0,28.